TINDAK TUTUR EKSPRESIF DAN STRATEGI BERTUTUR GURU DALAM PEMBELAJARAN MENGULAS KARYA FIKSI KELAS VIII SMP NEGERI 1 PASAMAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' responses to the expressive speech acts delivered by teachers in classroom interactions vary significantly, ranging from positive to negative feedback. This is often influenced by the appropriateness of the speech types and the communication strategies employed by the teacher. This study aims to analyze the variations of expressive speech acts and the speaking strategies used by Indonesian language teachers during the learning session on reviewing fictional works in class VIII of SMP Negeri 1 Pasaman. A descriptive qualitative method was employed, with data consisting of lingual units from teacher utterances containing expressive elements. Data collection was carried out through the techniques of non-participant observation (SBLC), recording, and note-taking. The research findings revealed 60 data points encompassing five categories of expressive speech acts: praising, blaming, apologizing, thanking, and criticizing. Furthermore, the speaking strategies implemented included bald on record, positive politeness, negative politeness, and off-record strategies. The results of the analysis indicate that praising speech acts and bald on record strategies were the most dominant communication instruments in the learning process.